The Comparison of Jigsaw Cooperative Learning Model with STAD on Mathematics Subjects in Junior High School - Kamid, kamid; Winarni, Sri; Rohati, Rohati; Rivani, Putri Ayu; Azzahra, Miftahul Zannah (Journal of Education Reseach and Evaluation, 2022)
The ability to think analytically is one of the competencies that must be possessed by students. Analytical thinking is a thinking ability that involves the process of breaking down material into small pieces and determining the relationships and overall structure. There are three levels of analytical thinking skills that students must have, namely the ability to remember, understand and be able to apply. Teachers are required to develop a learning model that is more innovative and fun in the learning process in order to stimulate students' analytical thinking by using the JIGSAW and STAD learning models to further hone their process skills. This study uses quantitative methods with associative and comparative types, where the data is taken using questionnaire respondents. The subjects of this study were 180 students. From the results obtained, it can be concluded that from the T test results, the difference in analytical thinking using the STAD model and using the Jigsaw model and the process skills variable using the STAD model and Jigsaw model in mathematics subjects. From the results of the correlation test, it is known that there is a relationship between analytical thinking and student process skills using the Jigsaw learning model. So that this research has an impact on the comparison of analytical thinking with student process skills using the JIGSAW and STAD learning models.